2021
DOI: 10.1111/jade.12359
|View full text |Cite
|
Sign up to set email alerts
|

Expanding from the Small Screen – Arts Practice for Affective Digital Presence

Abstract: Responding to conditions of lockdown and social distancing since March 2020, the Centre for Arts and Learning (CAL) at Goldsmiths is researching how arts practice and creative processes can sustain an affective presence in digital learning environments. In this article I discuss our research into how artist educators and students have adapted to the necessity for online learning, including the difficulties of doing so. I refer to a posthumanist, Deleuzian theoretical map that connects with the different collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…She describes how these zones of conflict and change present both challenges and opportunities through the creation of new liminal spaces as practice moves from the art gallery and studio into the digital realm and virtual imagined spaces. She invites us to find comfort in the discomfort, to celebrate the possibilities of a hybrid online practice and to explore the potential of the ‘affective turn’ within these liminal spaces to connect to share, to feel and to respond (Matthews 2021). Despite our initial discomfort and fear at having to move our learning programmes online, we worked together to find ways to overcome the challenges we faced.…”
Section: Discussionmentioning
confidence: 99%
“…She describes how these zones of conflict and change present both challenges and opportunities through the creation of new liminal spaces as practice moves from the art gallery and studio into the digital realm and virtual imagined spaces. She invites us to find comfort in the discomfort, to celebrate the possibilities of a hybrid online practice and to explore the potential of the ‘affective turn’ within these liminal spaces to connect to share, to feel and to respond (Matthews 2021). Despite our initial discomfort and fear at having to move our learning programmes online, we worked together to find ways to overcome the challenges we faced.…”
Section: Discussionmentioning
confidence: 99%
“…If we are to make use of the best of millennia of thinking about how we can best support and develop society, our learning and social strategies are called upon to build pedagogies that nurture, care and include. Initiatives such as Isolation Art School, the NSEAD Life after Lockdown project and the Centre for Arts and Learning's Finding Comfort within Discomfort research project (Matthews 2021), have found ways of forming structures for support and sustenance. The creative organisation of social protest has also demonstrated the strength of care for minority groups, as the mass movement Black Lives Matter calls out the need for the privileged white global minority to care more about equality for people of colour.…”
Section: Section 3: Resistant Collaborative Pedagogiesmentioning
confidence: 99%
“…Creative 'warm up' exercises are used in many fields: singers and athletes do warm up exercises, to keep a supple flow in practice. In the visual arts we set ourselves tasks such as drawing with the non-dominant hand and freely moving away from preconceived ideas (Matthews 2021). Therefore, it did not matter if the audience had done the same exercise beforeand this time it would be with a different form of attention, and different collective questioning processes.…”
Section: Section 4: Miranda's Part Of the Workhop: What Why Howmentioning
confidence: 99%
“…Arts educators and students might think of John Dewey's ‘learning by doing’ laboratory schools in their pragmatic approaches (Sadovnik et al. 2017), the introduction of strangeness that Rancière discusses (Rancière 2010; Matthews 2021), the re‐enchantment of everyday life encountered by Bennett (2001), or the intersectional approaches of Collins to the remarkable and wonderful protest interventions of art practice (2019).…”
Section: Introducing the Daily Extraordinarymentioning
confidence: 99%